Neighborhood Inequalities and the Long‐Term Impact of Foreclosures: Evidence from the Los Angeles–Inland Empire Region. (September 2016) - Molina, Emily Tumpson
Abstract : It is well documented that the foreclosure crisis was experienced unevenly in metropolitan regions nationwide. Yet it is still unclear how the long‐term impacts of the foreclosure crisis manifested within the American metropolis. This paper identifies where the long‐term negative impacts of the housing crisis were most acute by locating where foreclosed (REO) properties were more likely to remain vacant in the Los Angeles–Inland Empire area, a highly diverse region with high foreclosure rates. Foreclosure vacancies were concentrated in neighborhoods with larger Black and Latino populations, in older urban and inner‐ring suburban neighborhoods, and in poorer neighborhoods with poorly performing schools. These patterns illuminate the enduring and emerging sociospatial inequalities that contribute to contemporary neighborhood decline and will likely shape the Los Angeles region's future, further solidifying longstanding neighborhood and other social inequalities.